LIPID AND LIPOPROTEIN LEVELS IN HIV-INFECTED ADULTS WITH SEPSIS COMPARED TO HEALTHY HIV- INFECTED CONTROLS: Reduced lipoptorein levels in septic HIV infected adults - Seedat, Faheem; Raal, Frederick; Martinson, Neil; Variava, Ebrahim (African Journal of Infectious Diseases (AJID), 2020)
Background: In acute sepsis, reduced lipid and lipoprotein levels occur in HIV negative patients, in particular, low high-density lipoprotein cholesterol (HDL–c) levels are inversely correlated with sepsis severity and increased mortality. However, due to the limited data describing lipid and lipoprotein levels in septic HIV–infected individuals we aimed to investigate the changes in this subgroup. Materials and Methods: A prospective cross–sectional observational study of HIV–infected patients comparing admitted HIV – infected patients with sepsis to healthy controls from the antiretroviral therapy (ART) clinic. Non fasting - lipograms, ART use, diagnosis of tuberculosis (TB), markers of infection, renal function and mortality outcome to 3 months post discharge were reviewed. Results: Total cholesterol (TC), low–density lipoprotein (LDL–c) and HDL-c were all significantly lower in the sepsis group (p < 0.001). HDL–c was significantly associated with a higher white cell count (p = 0.018), higher C– reactive protein (p = 0.036) and low serum albumin (p < 0.001). In those with active TB (55%) HDL–c was reduced even further (0.55 vs. 0.72mmol/L, p = 0.013). Acute kidney injury (p = 0.560) and mortality at discharge (p = 0.097) or 3 months follow up (p = 0.953) was not associated with reduced HDL–c. Conclusion: Septic HIV–infected patients had significantly reduced lipid and lipoprotein levels at admission. Of note however, a low HDL–c was associated with markers of infection and reductions in HDL–c was more marked in those with active TB